2019
DOI: 10.12932/ap-100518-0309
|View full text |Cite
|
Sign up to set email alerts
|

Dengue vaccine: Global development update

Abstract: The first licensed dengue vaccine, CYD-TDV (Dengvaxia®), has received regulatory approval in a number of countries. However, this vaccine has some limitations. Its efficacy against DENV2 was consistently lower than other serotypes. Protective efficacy also depended on prior dengue sero-status of the vaccinees. Lower efficacy was observed in children with < 9 years old and dengue-naïve individuals. More importantly, risk of hospitalization and severe dengue was increased in the youngest vaccine recipients (2-5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
30
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 25 publications
0
30
0
1
Order By: Relevance
“…To resolve this significant, international public health problem, considerable effort has been directed toward the development of safe dengue vaccines. A number of candidates have been reported, including inactivated vaccines, live-attenuated vaccines, DNA vaccines, and subunit protein vaccines (Eckels and Putnak, 2003;Whitehead, 2016;Bustos-Arriaga et al, 2018;Manoff et al, 2019;Prompetchara et al, 2019;Wang et al, 2019). Of great concern, the first and only licensed dengue vaccine, Dengvaxia, had been approved for use in endemic areas owing to its higher efficacy among participants vaccinated at age ≥9 years (Ferguson et al, 2016;Henein et al, 2017); however, a post-hoc analysis of safety and efficacy reported a higher risk of severe dengue attack and hospitalization in vaccinated persons who had not been exposed to dengue (Sridhar et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…To resolve this significant, international public health problem, considerable effort has been directed toward the development of safe dengue vaccines. A number of candidates have been reported, including inactivated vaccines, live-attenuated vaccines, DNA vaccines, and subunit protein vaccines (Eckels and Putnak, 2003;Whitehead, 2016;Bustos-Arriaga et al, 2018;Manoff et al, 2019;Prompetchara et al, 2019;Wang et al, 2019). Of great concern, the first and only licensed dengue vaccine, Dengvaxia, had been approved for use in endemic areas owing to its higher efficacy among participants vaccinated at age ≥9 years (Ferguson et al, 2016;Henein et al, 2017); however, a post-hoc analysis of safety and efficacy reported a higher risk of severe dengue attack and hospitalization in vaccinated persons who had not been exposed to dengue (Sridhar et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The participation largely depends on peoples' knowledge, awareness and attitude towards this disease. But the effective dengue prevention and control is a burning question today in Bangladesh as there is an ongoing challenge to ensure proper treatment and prevention options despite having continued progress in dengue research [15,16]. In prior studies, it was shown that illiteracy, poverty and social incognizance are responsible factors for poor dengue management [17].…”
Section: Introductionmentioning
confidence: 99%
“…Despite continued progress in dengue research, it remains an ongoing challenge to identify definitive treatment and prevention options [20,21]. Therefore, it is of particular importance to reveal the genotypes of circulating DENV isolates distributed in different endemic countries, including Bangladesh, the focus of this article.…”
Section: Introductionmentioning
confidence: 99%